Update on Prepregnancy Maternal Obesity: Birth Defects and Childhood Outcomes - Iessa, Noha; Bérard, Anick (Journal of Pediatric Genetics, 2015)
Obesity is a growing global health epidemic. It is estimated that more than 20% of pregnancies are complicated by obesity. Prepregnancy obesity has been associated with birth defects such as neural tube defects, macrosomia, fetal death, and long-term effects such as asthma on the offspring. We provide a summary of the most recent studies and meta-analyses on obesity and birth outcome. Possible mechanisms of actions are explored and recommendations for further research are highlighted.
Keywords: obesity; body mass index; pregnancy; major congenital malformations